Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah, Kompetensi Sumber Daya Manusia, dan Pemanfaatan Teknologi Informasi terhadap Kualitas Laporan Keuangan pada Rumah Sakit Umum Daerah Ruteng - Flaviana Maria Rosari Edison; Herly M. Oematan; Junita Cestilia Nenabu (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of the implementation of a regional financial accounting system, human resource competency, and the utilization of information technology on the quality of financial reports at Ruteng Regional General Hospital (RSUD). The background of this research is based on the increasing demands for public accountability in the government sector, including RSUD. This study used a quantitative approach, with a population of 45 employees at Ruteng Regional General Hospital and a sample of 30 employees selected using a purposive sampling technique: employees working in the finance subdivision of Ruteng Regional General Hospital and employees working in the Planning, Evaluation, and Reporting subdivision. The results indicate that the implementation of a regional financial accounting system and the utilization of information technology have a significant impact on the quality of financial reports. Meanwhile, human resource competency does not have a significant impact on the quality of financial reports. In conclusion, the quality of financial reports at Ruteng Regional General Hospital is influenced by the regional financial accounting system and the utilization of information technology, while human resource competency has no significant impact.